Evaluation of recombinant plasmodium knowlesi merozoite surface Protein-1(33) for detection of human Malaria - Cheong, F.W.; Lau, Y.L.; Fong, M.Y.; Mahmud, R. (2013)
Plasmodium knowlesi is now known as the fifth Plasmodium species that can cause human malaria. The Plasmodium merozoite surface protein (MSP) has been reported to be potential target for vaccination and diagnosis of malaria. MSP-1(33) has been shown to be immunogenic and its T cell epitopes could mediate cellular immune protection. However, limited studies have focused on P. knowlesi MSP-1(33). In this study, an approximately 28-kDa recombinant P. knowlesi MSP-1(33) (pkMSP-1(33)) was expressed by using an Escherichia coli system. The purified pkMSP-1(33) reacted with serum samples of patients infected with P. knowlesi (31 of 31, 100) and non-P. knowlesi malaria (27 of 28, 96.43) by Western blotting. The pkMSP-1(33) also reacted with P. knowlesi (25 of 31, 80.65) and non-P. knowlesi malaria sera (20 of 28, 71.43) in an enzyme-linked immunosorbent assay (ELISA). Most of the non-malarial infection (49 of 52 in by Western blotting and 46 of 52 in the ELISA) and healthy donor serum samples (65 of 65 by Western blotting and ELISA) did not react with recombinant pkMSP-1(33).